Inhibition of p38 mitogen-activated protein kinase exerts a hypoglycemic effect by improving β cell function via inhibition of β cell apoptosis in db/db mice - Xiaowei Wei; Nan Gu; Nan Feng; Xiaohui Guo; Xiaowei Ma (Taylor & Francis Group, 2018)
The p38 mitogen-activated protein kinase (MAPK) pathway is involved in endoplasmic reticulum stress (ERS) and inflammation, which may play an important role in the pathogenesis of type 2 diabetes (T2DM). This study aimed to investigate whether p38 MAPK contributes to the pathogenesis of T2DM. 6-week-old female db/db mice were randomly assigned to Dmo and Dmi groups, and C57 mice were assigned as controls. The Dmi group was gavaged with the p38 MAPK inhibitor SB203580 for 9 weeks, and the effects on β cell dysfunction and apoptosis were investigated. db/db mice showed higher food intake, body mass, fasting glucose, and plasma insulin levels than C57 mice. After SB203580 administration, blood glucose was significantly lower. HOMA β and HOMA IR were improved. Islet mRNA expression levels of the ERS markers were lower. P38 MAPK inhibition reduced blood glucose and improved β cell function, at least in part by reducing β cell apoptosis.